2014
DOI: 10.1016/j.alcr.2014.03.001
|View full text |Cite
|
Sign up to set email alerts
|

When do socioeconomic resources matter most in early childhood?

Abstract: Research has established the importance of early socioeconomic advantage and disadvantage for understanding later life outcomes, but less is known about change in the relationship between socioeconomic status (SES) and child development within the period of early childhood. Competing hypotheses drawn from the literature posited: (1) a stable SES-development relationship, (2) a stronger relationship in infancy than at older ages, and (3) a stronger relationship at school entry than at younger ages. Using the na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 56 publications
0
20
0
1
Order By: Relevance
“…Literature suggests that the well-established social gradient in physical capability partly originates in early life [ 1 12 ]. The relation is suggested to pass through intermediate factors such as childhood growth and development (cognitive and physiological), adult socioeconomic position (SEP), health behavior and health status [ 5 , 13 ]. Childhood SEP could be of particular importance because of its impact on the physiologic reserve from which age-related decline begins [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Literature suggests that the well-established social gradient in physical capability partly originates in early life [ 1 12 ]. The relation is suggested to pass through intermediate factors such as childhood growth and development (cognitive and physiological), adult socioeconomic position (SEP), health behavior and health status [ 5 , 13 ]. Childhood SEP could be of particular importance because of its impact on the physiologic reserve from which age-related decline begins [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the association between maternal education and behavioral outcomes at 2 and 5 [ 1 2 7 _ T D $ D I F F ] years old emerged. A possible explanation for poorer developmental outcome at 2 years of age in the immediate delivery group, and the absence of this difference at 5 [ 1 2 7 _ T D $ D I F F ] years could be that environmental factors such as maternal education and socio-economic status become more important for development at older ages [33]. Additionally, if a developmental delay is noticed early, early interventions at daycare or school can improve later development [34,35].…”
Section: Results In the Context Of What Is Knownmentioning
confidence: 99%
“…At the second site, a Midwestern University, participants were recruited from local early childcare centers. As reading practices have been shown to differ across socioeconomic status (SES; Huebner, 2000 ), we assessed whether conditions differed by caregivers’ education, a core dimension of SES ( Molborn et al, 2014 ). Two ANOVA’s revealed that primary caregivers’ [ F (2,55) = 0.565, p = 0.571] and secondary caregivers’ [ F (2,54) = 0.405, p = 0.669] education did not differ by condition.…”
Section: Methodsmentioning
confidence: 99%